Physiological and psychological responses to 100 km cross-country skiing during 2 days - Väänänen, I. I.; Vihko, V. (The Journal of Sports Medicine and Physical Fitness, 2005)
Aim: Physical exercise can have beneficial as well as detrimental effects on body tissues. The purpose of this study was to examine how the body responds to a 2-day 100 km ski event. Methods: Two-day follow-up, field trial to measure changes in body mass, postural response of heart rate, pain perception, range of joint movement, muscle circumferences, vertical jump, creatine kinase (CK) and profile of mood state to repeated long distance cross-country skiing during 2 days. Subjects: 10 physically active men (34.8±9.7 y, 1.82±0.05 m, 76.1±6.6 kg, BMI: 23.0±1.5. kg·m-2) participating in the Finlandia Ski Race, covering a total distance of 100 km during 2 days. Results: Cardiorespiratory loading was high (over 85% of the maximal heart rate). However, leg measurements showed no signs of edema or a decline in flexibility or functional strength. Conclusion: Subjects with excellent aerobic fitness are able to ski at high intensity a total of 100 km over 2 successive days without any major adverse effects on the musculoskeletal system or mood state.